A relação entre referenciação e argumentação - Silva, Walleska Bernardino (2008)
This study, carried out in the area of Textual Linguistics, aimed at investigating the relationship between reference choices (referenciation), one of the various mechanisms which are associated with textuality, and the development of argumentative texts. Based on a concept of text understood as an interactive means for the construing of meaning, and regarding the subject as an interactive being, our study is based on a socio-cognitive perspective, and seeks to understand men s ability to express value judgment through linguistic choices of reference. In order to achieve our goals, we focused mainly on the nominal remissive forms whose antecedent was necessarily inserted in the co-text. The nominal anaphoric expressions analyzed in the study were described in relation to: type; nucleus-name; as well as determinants and modifiers of the nucleus-name. Thus, it was our purpose to identify: a) whether the type of nominal anaphora reflects a subjective use (manifestation); b) whether the nucleus-name of the anaphoric form is able to convey an argumentative meaning, and c) what is the level of importance of the determinants and modifiers of the nucleus-name in the development of the argumentative texts. The corpus used in the study, of qualitative and quantitative nature, was composed of 30 essays taken from three newspapers: Folha de S. Paulo, O Estado de São Paulo and Estado de Minas. Starting from the premise that referenciation is a process, we based our work mainly in the studies by Mondada; Dubois (2003), Apótheloz (2003), Maingueneau (2005) and Koch (2003a). The analysis showed a preference for unfaithful anaphor, with a general nucleusname and definite descriptions preceding the nucleus-name. Based on these findings, we believe that referential relations and argumentation are closely related in terms of function, mainly concerning the terms which accompany the nucleus-name, either before or after it. These terms play an important role concerning referenciation, due to the fact that they determine the way the referent is represented in discourse. This representation is marked through personal impressions, and it is because of this fact that argumentation is intimately linked to anaphoric expressions which present some type of determinant. Among the determinants, the definite article is the most frequent one, and it is favored by the presence of another modifier in the same anaphoric expression, such as the prepositional phrase or a relative sentence.